Respostas ecofisiológicas de Cybistax antisyphilitica Mart. (Ipê verde) em função das alterações na intensidade de luz - Freitas, Fernanda Monteiro de (2016)
Light varies widely in both time and space in forest formation of “Bioma Cerrado”. Cybistax antisyphilitica occurs in areas typical of this biome, such as cerrado sensu stricto, “cerradões”, and altered areas. The aim of this study was to understand the morphological and physiological responses of C. antisyphilitica to alterations in light intensity. Juvenile plants (5 month of age) were taken to a fragment of semideciduous forest in Uberlândia-MG, and were divided into three treatments: 50 were maintained under the canopy (UC) 20 were kept in small gap (SG) and 20 were maintained under in full sun (FS). The daily courses of chlorophyll a fluorescence were made at the beginning, middle and end of dry season in 2015. At the end of the experiment measurements of chlorophyll content, gas exchange and growth were made. The plants showed dynamic photoinhibition as exhibited by reductions on Fv/Fm close to midday at the end of the dry season. Regarding the effective quantum yield (ΔF/Fm'), plants under FS showed reduced values that coincided with the higher values of electron transport rates (ETR). Plants under FS showed higher values of net CO2 assimilation rates, stomatal conductance, transpiration rates, water use efficiency and chlorophyll content compared to plants under UC. The stem diameter, dry mass of leaves and stem, total dry mass and relative growth rate were higher in plants under FS than plants under UC. On the other hand, plants under UC showed superior values of height, specific leaf area and leaf area ratio. Our results indicate that C. antisyphilitica has plasticity to survive in the contrasting light environments of the semideciduous forests, but this species was able to growth better under full sun conditions.